La gimnasia básica en el mejoramiento de la motricidad en estudiantes de básica - Quito Viveros, Freddy Enmanuel; Ordoñez Yaguana, Mercedes Estefanía (Machala: Universidad Técnica de Machala, 2023)
The present project was oriented towards basic gymnastics in the improvement of motor skills, with the purpose of identifying the time used by the teacher of the curricular block of gymnastic practices in physical education classes for the contribution and improvement of motor skills, in addition to determining What didactic resources and sports implements does the Jorge Icaza school have for the development of gymnastic practice as an effective means for the progress of motor skills, finally to diagnose the teacher's experience on gymnastic practice for the strengthening of motor skills in sub-level students of upper basic The data selection was based on a qualitative approach using a non-experimental descriptive method to successfully diagnose the problem of the Jorge Icaza school. The most successful methods in this investigation are the analytical-synthetic and the bibliographic, since they contributed considerably at the time of obtaining the information based on the specific objectives to contribute to the general objective, which were written to cover aspects related to the review. literature, with field research and finally to support the integrative proposal, as a contribution in favor of the educational institution that facilitated access to carry out the research. In relation to the sample, it was not obtained since the population of the institution is small. The selected instruments were the interview and the observation, which for its elaboration related the objects of study, whose investigation was derived from four dimensions and in effect the indicators served as a guide for the elaboration of the qualitative investigation instruments, which facilitated the reception opinions and attitudes of the people involved in this work and at the same time analyze the information obtained. The results of this research were addressed to physical education teachers to stimulate by means of an exercise guide on basic gymnastics that will favor the improvement of motor skills. In addition, this research includes a proposal that was elaborated in three phases of implementation aimed at, physical education teachers, Likewise, the logistical resources and the feasibility assessment were included with the dimensions, technical, economic, social and environmental, expressing the capacity to achieve the objectives of the proposal, establishing the feasibility and the materials with which the proposal was taken into account.
El presente proyecto se orientó hacia la gimnasia básica en el mejoramiento de la motricidad, teniendo como propósito, identificar el tiempo que utiliza el docente del bloque curricular de prácticas gimnásticas en las clases de educación física para la contribución y mejoramiento de la motricidad, además determinar con qué recursos didácticos e implementos deportivos cuenta el colegio Jorge Icaza para el desarrollo de la práctica gimnástica como medio eficaz para el progreso de la motricidad, finalmente diagnosticar la experiencia del docente sobre la práctica gimnástica para el fortalecimiento de la motricidad en los estudiantes del subnivel de básica superior. La selección de datos se basó en un enfoque cualitativo utilizando un método descriptivo no experimental para diagnosticar con éxito la problemática del colegio Jorge Icaza. Los métodos de mayor acontecimiento en esta indagación es el analítico-sintético y el bibliográfico, puesto que aportaron considerablemente al momento de obtener la información con base a los objetivos específicos para contribuir al objetivo general, mismos que estuvieron redactados para abarcar aspectos relacionados con la revisión literaria, con la investigación de campo y finalmente para sostener la propuesta integradora, como aporte a favor de la institución educativa que facilitó el acceso para concretar la investigación. En relación a la muestra, no se la obtuvo. Los instrumentos seleccionados fueron la entrevista y la observación, que para su elaboración se relacionó los objetos de estudio, cuya investigación se derivó de cuatro dimensiones y en efecto los indicadores sirvieron de guía para la elaboración de los instrumentos de investigación cualitativa, que facilitó la recepción de opiniones y actitudes de las personas involucradas en este trabajo y al mismo tiempo analizar la información obtenida. Los resultados de esta investigación fueron dirigidos a los docentes de educación física para estimular mediante una guía de ejercicios sobre la gimnasia básica que favorecerá al mejoramiento de la motricidad. A demás esta investigación incluye una propuesta que estuvo elaborada de tres fases de implementación dirigidas a, los docentes de educación física, asimismo se incluyó los recursos logísticos y la valoración de la factibilidad con las dimensiones, técnica, económica, social y ambiental, manifestando la capacidad para lograr los objetivos de la propuesta, estableciendo la viabilidad y los materiales con los que fueron tomados en cuenta la propuesta.
Keywords: GIMNASIA BASICA; MOTRICIDAD; EDUCACION FISICA; DESARROLLO